Eflornithine for chemoprevention in the high-risk population of colorectal cancer: a systematic review and meta-analysis with trial sequential analysis - Yang, Lifeng; Wang, Yan; Hu, Shasha; Wang, Xiaoyan (Frontiers in Oncology, 2023)
Objectives To evaluate the efficacy of Difluoromethylornithine (DFMO) chemoprevention in the high-risk population for colorectal cancer (CRC).Methods Meta-analysis was conducted to assess the caliber of the included literature by searching five databases for randomized controlled trials of DFMO chemoprevention in the high-risk population of CRC, with RevMan 5.4, Stata 15.0 and TSA 0.9.5.10 employed to statistically analyze the extracted data. Grade profiler 3.6 was employed for grading the evidence for the outcome indicators (disease progression and adenoma incidence).Six trials were finally included in this research, with the collective data indicating that the DFMO combination therapy was efficacious in lowering the incidence of recurrent adenomas in patients who had experienced advanced CRC [RR 0.34, 95% CI 0.14 -0.83, P < 0.05]. Meta-analysis showed that DFMO combined therapy had no statistical difference in disease progression in patients with familial adenomatous polyposis[RR 0.52, 95% CI 0.14 -1.86, P > 0.05]; Trial Sequential Analysis reveals that the combination therapy of DFMO effectively diminishes the occurrence of recurrent adenomas in patients with a history of advanced colorectal tumors, displaying a Risk Ratio (RR) of 0.33 with a 95% Confidence Interval (CI) of 0.12 -0.90 and a significance level of P < 0.05. This combination exhibits a statistically significant difference. Subgroup analysis demonstrates that, depending on the drug treatment regimen (DFMO+ Aspirin/DFMO+ Sulindac), the combination of DFMO and aspirin exhibits an effect comparable to a placebo in diminishing the occurrence of new adenomas in patients with a history of advanced colorectal tumors. However, the combination of DFMO and sulindac significantly mitigates the incidence of recurrent adenomas in this patient population.This meta-analysis indicates that the existing randomized controlled trials are adequate to ascertain the efficacy of DFMO combination therapy in diminishing the incidence of recurrent adenomas in patients who have previously encountered advanced colorectal tumors. However, further clinical trials need to be conducted to evaluate the optimum dosage and treatment course of prophylactic implementation of DFMO combination therapy in high-risk populations.